2020
DOI: 10.3390/molecules25163606
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Secretome from Fat Tissues on Ion Currents of Cardiomyocyte Modulated by Sodium-Glucose Transporter 2 Inhibitor

Abstract: Sodium-glucose transporter 2 (SGLT2) inhibitors were shown to decrease mortality from cardiovascular diseases in the EMPA-REG trial. However, the effects of empagliflozin (EMPA) for cardiac arrhythmia are not yet clarified. A total of 20 C57BL/6J mice were divided into four groups: (1) The control group were fed standard chow, (2) the metabolic syndrome (MS) group were fed a high-fat diet, (3) the empagliflozin (EMPA) group were fed a high-fat diet and empagliflozin 10 mg/kg daily, and (4) the glibenclamide (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 32 publications
1
19
0
1
Order By: Relevance
“…These modifications of adipocytokines by SGLT2 inhibitors and sulfonylurea treatment have been elucidated in a previous study [ 25 ]. In our previous study, the ion currents of cardiomyocyte could be modulated by adipocytokines after EMPA treatment, which might provide a possible mechanism for the antiarrhythmic effect [ 10 ]. In the EMPA-REG study, EMPA also showed benefits for patients with heart failure treatment and for the prevention of sudden cardiac death [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These modifications of adipocytokines by SGLT2 inhibitors and sulfonylurea treatment have been elucidated in a previous study [ 25 ]. In our previous study, the ion currents of cardiomyocyte could be modulated by adipocytokines after EMPA treatment, which might provide a possible mechanism for the antiarrhythmic effect [ 10 ]. In the EMPA-REG study, EMPA also showed benefits for patients with heart failure treatment and for the prevention of sudden cardiac death [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also shown that SGLT2 inhibitors do not prolong the QT interval on electrocardiography, alleviate atrial remodeling, and improve mitochondrial function in diabetic rats [ 8 , 9 ]. We previously demonstrated that EMPA could modulate the effects of adipocytokines from fat tissues on the ion currents of cardiomyocytes and reduce arrhythmogenesis [ 10 ]. The effects of SGLT2 inhibitors, especially EMPA, on ventricular electrophysiological substrates have not been elucidated completely.…”
Section: Introductionmentioning
confidence: 99%
“…mRNA collagen type III was increased in diabetic mouse atria, likely contributing to the interstitial atrial fibrosis observed in diabetic mice 77 . A recent study demonstrated that EAT‐released proteins can downregulate the delayed rectifier K + outward currents and increase L‐type calcium channel currents 78 . In addition, other ex vivo studies have demonstrated the effects of the pericardial secretome on the activation time and conduction velocity of atrial cells 79 .…”
Section: Pathophysiological Mechanisms Of Af Related To Eatmentioning
confidence: 99%
“…In mice with metabolic syndrome, adipokines induced a decrease in the expression level of potassium channels and an increase in the expression levels of calcium channels. Empagliflozin pretreatment could attenuate this effect in mice with metabolic syndrome, potentially reducing the risk of arrhythmias due to a disturbed ion homeostasis [72]. For the other SGLT2 inhibitors canagliflozin and ertugliflozin, as well as for the combined SGLT1/SGLT2 inhibitor sotagliflozin, no data regarding antiarrhythmic effects have been published so far.…”
Section: Heart Failure and Diabetes: Ventricular Arrhythmiasmentioning
confidence: 99%